Pendampingan Penanaman Kenaf Sebagai Tanaman Alternatif Pasca Tanaman Jagung Di Desa Suradadi Kabupaten Tegal - Wiyanti, Sari (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
This community service determines the partners, namely the Suradadi village corn farmer group. The low income of farmers from rice fields has resulted in many farmers changing jobs and selling their fields. Farmers are reluctant to plant in rice fields in the dry season because of the high risk of losses in agricultural operational costs, namely superior seeds, fertilizers, pesticides, labor costs. rent irrigation generators and purchase water for irrigating rice fields. The problem farmers have is not knowing which plants are suitable for their land when they enter the dry season. The PKM team's solution to partners is to use land for planting kenaf. The method for implementing this community service is discussion, outreach and mentoring to partners. As a result of this community service, partners were able to participate in PKM activities from seeding to harvest for 4 months. The results obtained from an area of ​​7000 m2 were 51 tons of kenaf stems, if processed into kenaf fiber, 3 tons were obtained. From planting kenaf, the partners obtained additional income from selling kenaf fiber amounting to IDR 18,330,000.00. It can be concluded that partners can manage land in the dry season for planting kenaf, while still paying attention to land irrigation.